INTERACTIVE MULTIMEDIA AS INSTRUCTIONAL MEDIA FOR ELEMENTARY SCHOOL STUDENTS - Ratumbuisang, Keith Francis; Ratumbuisang, Yosua Fitsgerald (Information Technology Education Department, 2023)
The purpose of this research id to develop an interactive multimedia as instructional media with Adobe Animate application on computer introduction material. To determine the feasibility of the interactive multimedia requires expert judgment in terms of materials and media as well as students. This is a Research and Development (R&D) which adapted from the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), but only carried out until the Implementation. Validation is carried out by material experts, media experts, teachers, and students. Data collection techniques in this development research use a questionnaire. Data obtained from the questionnaire was then analyzed descriptively qualitatively and quantitatively. Based on four assessments which are material expert, media expert, teachers and students’ assessment, the level of feasibility of developed interactive instructional media is valid and worthy of being used as a computer introduction instructional media for Elementary school students. Thus, the use of this media helps connect students with enjoyable learning experience. As a result, a positive consequence of utilizing this interactive instructional media is that teacher must keep their materials up to date.